Biochanin A Inhibits Glioblastoma Growth via Restricting Glycolysis and Mitochondrial Oxidative Phosphorylation - Dong, Qiang; Li, Qiao; Duan, Lei; Yin, Hang; Wang, Xiaoqing; Liu, Yang; Wang, Bo; Li, Kun; Yao, Xuan; Yuan, Guoqiang; Pan, Yawen (Frontiers in Oncology, 2021)
Abnormal metabolism serves a critical role in glioblastoma (GBM). Biochanin A (BCA), a flavonoid phenolic compound found in edible and herbal plants, has antioxidative and antitumor activities. However, it remains unclear whether BCA has an effect on energy metabolism. The aim of the present study was to evaluate the anticancer effects and molecular mechanism of the effect of BCA on energy metabolism. We observed that BCA inhibited the growth of U251 cells by the mitochondria-mediated intrinsic apoptotic pathway. BCA treatment reduced metabolic function, repressed mitochondrial membrane potential, and increased the production of reactive oxygen species (ROS) in GBM. In addition, we found that BCA decreased aerobic glycolysis by inactivation of the AKT/mTOR pathway. Taken together, the results demonstrate that treatment with BCA inhibited the proliferation of GBM by regulating metabolic reprogramming.